Procedural scheduling (Revista do Tribunal Regional Federal da 3ª Região, 2015)
The aim of this paper is to analytically and pragmatically address the institute of calendaring. It is a technique for the rational management of procedural time, common in Anglo-Saxon countries. In these countries, scientific case management is adopted due to the influence of corporate governance ideas adapted to the jurisdictional sphere. This management technique promotes the end of “useless time” spent on office activities, since all the acts of the procedure are previously scheduled in a timetable imposed ab initio by the judge, or negotiated between the parties at a prior hearing. This makes it unnecessary, for example, for official acts of a mere expedient nature to move the process along and for them to be published in the official press.
Keywords: timetabling; procedural flexibility; procedural agreement; procedural manegerialism; case management; judicial governance; procedural business